Handwashing among caregivers of young children in a protracted and complex refugee and immigration context: a mixed methods study on the Thai–Myanmar border - Pooseesod, Kasama; Umezaki, Masahiro; Phetrak, Athit; Phuanukoonnon, Suparat (Frontiers in Public Health, 2023)
Introduction Protracted refugee situations create complex contexts that present significant health risks for young children. Effective hand hygiene practices by caregivers can reduce respiratory infections and diarrhoeal disease, the two largest contributors to mortality among children between 1 month and 5 years of age. This study documented handwashing patterns and access to water, sanitation and hygiene (WASH) infrastructure among caregivers of young children living along the Thai–Myanmar border, one of the world’s most protracted and complex refugee and immigration contexts. It also examined the association between handwashing and socio-demographic variables and captured participants’ explanations for when and how hands are washed. The study broadened the scope of previous research by also including the large number of caregivers living outside formal camps. Methods Caregivers of children attending 11 preschools in Tak province, Thailand participated in a mixed-methods cross-sectional study. Quantitative questionnaire data (n = 384) were supplemented by a thematic analysis of data from in-depth interviews (n = 9). Results Fewer than half the caregivers reported routinely washing their hands before preparing meals or after using the latrine/toilet. Fewer than one-in-five routinely used soap in these situations. Interviewees explained that handwashing was only necessary when a substance could be felt or seen, in which case wiping with a cloth or a rinsing with water were sufficient to clean hands. However, their explanations also suggested some potential avenues for culturally appropriate and feasible interventions to improve hand hygiene. Conclusion The results confirmed previous research on the multi-dimensional barriers to good hand hygiene in protracted refugee situations and other low-resource settings. Additional investment to overcome shortages in the infrastructure necessary to support good hand hygiene and creative means of drawing on and developing human capital will be necessary to realize the potential hand hygiene holds for reducing ill-health and mortality among young children living in these contexts.